A Novel Antithrombotic Mechanism Mediated by the Receptors of the Kallikrein/Kinin and Renin–Angiotensin Systems - Schmaier, Alvin H. (Frontiers in Medicine, 2016)
The contact activation (CAS) and kallikrein/kinin (KKS) systems regulate thrombosis risk in two ways. First, the CAS influences contact activation-induced factor XI activation and thrombin formation through the hemostatic cascade. Second, prekallikrein (PK) and bradykinin of the KKS regulate expression of three vessel wall G-protein-coupled receptors, the bradykinin B2 receptor (B2R), angiotensin receptor 2, and Mas to influence prostacyclin formation. The degree of intravascular prostacyclin formation inversely regulates intravascular thrombosis risk. A 1.5- to 2-fold increase in prostacyclin, as seen in PK deficiency, increases vessel wall Sirt1 and KLF4 to downregulate vessel wall tissue factor which alone is sufficient to lengthen induced thrombosis times. A twofold to threefold increase in prostacyclin, as seen the B2R-deficient mouse, delays thrombosis and produces a selective platelet function defect of reduced GPVI activation and platelet spreading. Regulation of CAS and KKS protein expression has a profound influence on thrombosis-generating mechanisms in the intravascular compartment.